Limitation Of Liability And Third Parties - Berry, Brian (Journal of Malaysian and Comparative Law, 2019)
In insurance law, the issue may arise whether and to what extent a third party can avail himself of an immunity, a limitation of liability or other defence which is based on the insurance contract made by the assured with the insurer but intended by them, either expressly or impliedly, to benefit him. The problem arises most frequently when the insurer is pursuing subrogation proceedings against the wrong doing third party.